Assessment of the implementation fidelity of a strategy to scale up integrated care in five European regions: a multimethod study. Issue 3 (18th March 2020) - Grooten, Liset; Fabbricotti, Isabelle Natalina; Devroey, Dirk; Vrijhoef, Hubertus J M
Abstract : Objective: The SCaling IntegRated Care in COntext (SCIROCCO) project tested a step-based scaling up strategy to explore what and how to scale up integrated care initiatives in five European regions. To gain a profound understanding of which factors influence the implementation of this strategy, the objective of this study was to assess the extent to which the SCIROCCO strategy was implemented as planned. Design: Multimethod study. Methods: The extended version of the conceptual framework for implementation fidelity was used to evaluate what factors influence the implementation of the scaling up strategy. Data were collected in the five participating European regions during the intervention period. Data collection methods included: key informant interviews, focus groups, questionnaire studies and project documents. Results: All three main steps of the scaling up strategy were implemented with acceptable fidelity. Variations were observed in the duration of implementing the steps in the regions. Also, variations were observed in the coverage of experts to participate in the steps of the strategy. Several factors were observed to influence the implementation: facilitation conditions (ie, good coordination for implementation) and participant responsiveness (ie, a positive experience of participants in the organised study visits). Factors that may have moderated adherence to the original plan of the strategy were found in facilitating conditions (ie, in the flexible approach), participant recruitment factors (ie, adaptions of the procedure by the regions) and contextual factors (ie, the level of development of integrated care). Conclusion: This was the first study to assess implementation fidelity of a European project that used a step-based scaling up strategy in five European regions. Similar European projects that are based on collaboration between several European regions can learn from the lessons captured in SCIROCCO and can become more aware of the facilitating factors and pitfalls of implementing such projects.